Product inhibition of secreted phospholipase A2 may explain lysophosphatidylcholines' unexpected therapeutic properties - Lucena Angel; Yao Lihua; Cunningham Timothy J (BMC, 2008)
Abstract Background Lysophosphatidylcholines (lysoPCs) are products of phospholipase A2 (PLA2) enzyme activity, and like the enzyme, have a direct role in toxic inflammatory responses in variety of organ systems. Paradoxically, reduced plasma lysoPC levels have been noted in sepsis patients and systemic treatment with lysoPCs is therapeutic in rodent models of sepsis and ischemia. These observations suggest that elevation of plasma levels of these lipids can actually help to relieve serious inflammatory conditions. We demonstrate that specific lysoPCs act as uncompetitive product inhibitors of plasma secreted PLA2 enzymes (sPLA2s), especially under conditions of elevated enzyme activity, thus providing a feedback mechanism for the observed anti-inflammatory effects of these compounds. Methods Thin layer chromatography and mass spectroscopy were used to estimate total lysoPC concentration and the relative contributions of different lysoPC species in rat plasma samples. Kinetic studies of sPLA2 enzyme activity were conducted on these samples ex vivo and on purified group IA sPLA2 in vitro after addition of specific lysoPC species to the reaction mixture. Enzyme activity was also measured in plasma samples of rats injected with these same lysoPCs. Results Palmitoyl (16:0), stearoyl (18:0) are the most abundant lysoPCs in rat plasma consistent with other reports. Kinetic studies demonstrated that both were uncompetitive inhibitors of plasma sPLA2 enzyme activity. In vitro experiments with group IA sPLA2 confirmed the inhibition and the kinetic properties of these lysoPC species. Decanoyl lysoPC (10:0), which was not detected in plasma, did not inhibit enzyme activity in vitro. LysoPC injections into normal rats resulted in "buffering" of plasma sPLA2 activity in a narrow low range, consistent with the activity-dependent inhibition suggested by the ex vivo and in vitro experiments. Conclusion The results may explain the efficacy of lysoPC therapy during periods of elevated inflammatory activity and further highlight the utility uncompetitive enzyme inhibitors. In this case, the inhibitor is a product of the enzyme reaction, and therefore represents an example of activity-driven feedback inhibition.